KONSEP AL-QUR`AN TENTANG âADILâ DALAM PERNIKAHAN POLIGAMI (Sebuah Studi Tafsir Dengan Pendekatan Tahlili ) - Harahap, Ikhwanuddin (Institut Agama Islam Negeri Padangsidimpuan, 2018)
Islam came to jahiliyah community and reformed some institutions of arabic cultures and laws. One of them was regulation of poligamy. Islam limited it in 4 (four) wives maximally, meanwhile it wasnât limited in arabic law. The prerequest of the poligamy is âadil. âadil is the problematic issue in islamic thought. Some scholars say that it is impossible for husband to make âadil between his wives, meanhile some of them say that is possible. This paper aims to show how al-quran describes the âadil on poligamy by tahlili approach.